Gender analysis of sweetpotato value chains: The impact of introducing orange-fleshed varieties to industrial buyers in Homa Bay and Bungoma, Kenya - Mudege, Netsayi N.; Kwikiriza, N.; Heck, S. (International Potato Center, 2020)
Under the auspices of the CIP‐led Scaling Up Sweetpotato through Agriculture and Nutrition project (SUSTAIN), the study reported here sought to understand how the introduction and commercialization of orange-fleshed sweetpotato has affected opportunities and constraints for smallholder sweetpotato farmers, particularly women. A social relations approach was used for the study which included surveys, in‐depth interviews, focal groups discussions, and analysis of existing data. Data collection was carried out in March 2018.